2014
DOI: 10.1007/s13280-014-0519-6
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Impacts of Climate Change on Current Farming Locations of Striped Catfish (Pangasianodon hypophthalmus; Sauvage) in the Mekong Delta, Vietnam

Abstract: In Vietnam, culturing striped catfish makes an important contribution to the Mekong Delta's economy. Water level rise during rainy season and salt intrusion during dry season affect the water exchange and quality for this culture. Sea level rise as a consequence of climate change will worsen these influences. In this study, water level rise and salt water intrusion for three sea level rise (SLR) scenarios (i.e., ?30, ?50, and ?75 cm) were simulated. The results showed that at SLR ?50, the 3-m-flood level would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…It was suggested that the climatic change impacts or increased temperature (=global warming) would be likely to have minimal impacts on aquaculture ). On the other hand, freshwater farming systems near to the coasts are likely to be impacted by sea level rise and concurrent seawater intrusion coupled with water scarcity, such as the pangasius (Pangasianodon hypophtalmus) farming systems in the Mekong Delta, Vietnam (Nguyen et al 2014). As such there is a need to encourage work on climate-change impacts on freshwater farming systems in China, and consequently to develop mitigating and adaptive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the climatic change impacts or increased temperature (=global warming) would be likely to have minimal impacts on aquaculture ). On the other hand, freshwater farming systems near to the coasts are likely to be impacted by sea level rise and concurrent seawater intrusion coupled with water scarcity, such as the pangasius (Pangasianodon hypophtalmus) farming systems in the Mekong Delta, Vietnam (Nguyen et al 2014). As such there is a need to encourage work on climate-change impacts on freshwater farming systems in China, and consequently to develop mitigating and adaptive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Sea-level rise has the potential to affect coastal aquaculture operations through loss of culture area (Hargreaves 2014), greater and more distant salt intrusion into coastal groundwater (Ahmed 2013, Nguyen et al 2014, Smajgl et al 2015, Tully et al 2019, and, in some areas, the augmentation of seasonal or episodic flooding via storm surges (Wassmann et al 2004, Rhein et al 2013. Global mean sea level rose 1.2 ± 0.2 mm yr −1 between 1901 and 1990, with this rate increasing to 3.0 ± 0.7 mm yr −1 between 1993 and 2010 (Hay et al 2015).…”
Section: Sea-level Risementioning
confidence: 99%
“…Rice cropping systems in the Mekong delta have shown signs of stress in response to an increasing number of severe floods, droughts, storms and tropical cyclones, followed by growing population demand for food production (Lusterio 2009;Nguyen 2011;Berg and Tam 2012;Huysveld et al 2013;Son et al 2013;Ahmed et al 2014). Food production systems are rapidly expanding into the flood and salinity-intrusion areas (Tuong et al 2003;Kotera et al 2014), as a result of engineering works aimed at protecting populations and infrastructure from storms, rice cropping systems and shrimp farms from saltwater intrusion (Berg et al 2012;Nguyen et al 2014). The construction of several large-scale dams, and major channel-bed mining activities (Piman et al 2013), have now been reported as the cause of an imbalance between flow and sediment entrainment conditions (Xue et al 2011), affecting human livelihoods and the ecological equilibrium in the delta.…”
Section: Mekongmentioning
confidence: 99%
“…The construction of several large-scale dams, and major channel-bed mining activities (Piman et al 2013), have now been reported as the cause of an imbalance between flow and sediment entrainment conditions (Xue et al 2011), affecting human livelihoods and the ecological equilibrium in the delta. Predictions of exposure to the effects of climate change for the Mekong delta include a rising sea level, rising temperatures, increased variability in rainfall regime and higher frequency of extreme events (Kotera et al 2008;Haruyama and Ito 2009;Nguyen et al 2014). These changes are likely to have strong negative impacts on the production of food and human wellbeing (Nguyen 2011;Berg et al 2012;Berg and Tam 2012;Kotera et al 2014).…”
Section: Mekongmentioning
confidence: 99%
See 1 more Smart Citation